In situ modification of three-dimensional polyphenylene dendrimer-templated CuO rice-shaped architectures with electron beam irradiation - Qi, Xiaoying (2012)
In this study, the high-energy electron beam of the transmission electron microscope (TEM) is utilized as an external force to in situ modify the polyphenylene dendrimer (G2Td(COOH)16) templated CuO rice-shaped architecture (RSA). By virtue of the nanoscale precision of this approach, the electron beam-modified RSA retains its rice shape while the internal primary CuO nanoparticles are converted to the Cu2O nanoparticles with increased size. Detailed investigation using a time-lapse TEM technique reveals that such a modification process is mainly constituted by two stages, involving the arrangement of the primary CuO nanoparticles and the transformation of the primary CuO into Cu2O nanoparticles. Within the modification process, the high-energy electron beam of TEM serves as the external driving force and energy resource to improve the orientation and increase the crystallinity of the single-phase CuO nanoparticles and subsequently transfer the nanoparticle phase from CuO to Cu2O. This study highlights a facile in situ way to finely tune the nanoscale morphology and chemical composition of nanoparticles and nanoparticle-based assembled structures.